The Application of Problem-Based Learning Methods to Increase Learning Outcomes in News Item Text Material - Nur'anisa, Siti; Korompot, Chairil Anwar; Nawir, Nurdiana (ETDC: Indonesian Journal of Research and Educational Review, 2024)
In the world of education, of course, we are no strangers to the problem-based learning method, where learning should be student-centered, which was initially oriented to a problem related to the topic of learning. The author intends to implement the PBL method in the news item text learning process at MAN Lamandau, particularly in class XII. This study seeks to understand its application, the students' comprehension of the material, and their involvement in the news item text learning process. The author used data from his field experience practice at MAN Lamandau, specifically in class XII, for the discussion. The author carried out the learning process himself using the PBL method with the text topics mentioned above. Later, the author will use a qualitative method in the form of a narrative to convey the results. Despite several challenges in the implementation process, including the absence of an interactive discussion process due to students' passive tendencies and external factors that disrupt the learning process, the PBL method's application generally piques students' interest and motivation in the news item text learning process, as they typically receive only lectures.